The Don Cossacks of the Late 19th – Early 20th c. in Shane O’Rourke’s Book “Warriors and Peasants: The Don Cossacks in Late Imperial Russia” (Shane O’Rourke. Warriors and Peasants: The Don Cossacks in Late Imperial Russia. – New York : St. Martin’s, in Association with St. Antony’s College, Oxford, 2000. – 200 p.) - Alexey A. Volvenko; Antonina I. Mitrofanova (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. The article analyzes the contents of the monograph “Warriors and Peasants: The Don Cossacks in Late Imperial Russia” of modern English historian Shane O’Rourke, who is the prominent representative of western English-language historiography.